Global Health in Africa : Historical Perspectives on Disease Control - Webb, James L. A., Jr., 1952-; Giles-Vernick, Tamara, 1962- (Book collections on Project MUSE., 2013)
Global Health in Africa is a first exploration of selected histories of global health initiatives in Africa. The collection addresses some of the most important interventions in disease control, including mass vaccination, large-scale treatment and/or prophylaxis campaigns, harm reduction efforts, and nutritional and virological research. The chapters in this collection are organized in three sections that evaluate linkages between past, present, and emergent. Part I, "Looking Back," contains four chapters that analyze colonial-era interventions and reflect upon their implications for contempo